Constipation in patients treated with opioids: an integrative review - de Lima, Martiniano Bezerra (2017)
Objective: To investigate the impact of Opioid-Induced Constipation (OIC) in the literature through the identification of the risk factors, symptoms and treatments. Methods: We carried out a review of scientific publications available in the Virtual Health Library (VHL), the Scientific Electronic Library Online (SciELO), the Latin-American and Caribbean Center on Health Sciences Information (LILACS) and the Medical Literature Analysis and Retrieval System Online (MEDLINE) databases. The search was carried out using the descriptors “analgesic opioids”, “constipation” and “pain” in English, Portuguese and Spanish, correlated or isolated. We searched for publications dating from 2011 to 2016 that investigated patients receiving treatment for pain with continuous use of opioids and with constipation as a clinical outcome. Results: The results highlighted constipation as the main secondary effect of opioids, which are very important for the control of cancer pain, and identified the risk factors for the disease. In addition, patients who were well served by health professionals presented better adherence to OIC treatment. Conclusion: The OIC control provides abdominal comfort, self-care and reduction in treatment costs. The importance of training health professionals and promoting prevention and periodic monitoring of patients should be highlighted. In addition, diet therapy and drug therapy should be provided early.